Gold nanoparticles embedded in carbon film: Micromorphology analysis - Ţălu, Ştefan; Bramowicz, Miroslaw; Kulesza, Slawomir; Solaymani, Shahram; Shafikhani, Azizollah; Ghaderi, Atefeh; Ahmadirad, Mohammad (Journal of industrial and engineering chemistry (Seoul, Korea), 2016)
•We characterized three-dimensional surface texture analysis of Au NPs @ a-C: H films.•We used atomic force microscopy and fractal geometry.•We determined the Areal Autocorrelation Function (AACF) and pseudo-topothesy K.•We determined statistical and fractal properties.•We determined the spatial distribution and pattern of surface characteristics. In this paper the sputtered gold nanoparticles (NPs) deposited by Radio Frequency-Plasma Enhanced Chemical Vapor Deposition (RF-PECVD) method on the glass substrates in trace of amorphous hydrogenated carbon (Au NPs @ a-C: H) were analyzed to study the three-dimensional (3-D) surface texture. The prepared Au NPs @ a-C: H films were used as research materials. The synthesis of samples was carried out in different powers from 80 to 120W while all other parameters were kept constant. The X-ray diffraction patterns and UV–vis spectra were applied to study the structure and Localized Surface Plasmon Resonance (LSPR), respectively. An atomic force microscope in a non-contact mode was used to record the sample surface images then the fractal geometry was studied. The images were numerically processed to calculate the Areal Autocorrelation Function (AACF), which was used to determine the anisotropy ratio Str, and to compute the Structure Function (SF). The log–log plots of the latter were used to calculate fractal properties of the studied surfaces, such as fractal dimension D, and pseudo-topothesy K. The analysis of 3-D surface texture was helpful in optimizing the functional performance of the thin film.